HUBUNGAN WAKTU RESPON TIME PELAYANAN INSTALASI GAWAT DARURAT DENGAN KEPUASAN PASIEN DI RUMAH SAKIT MUHAMMADIYAH SELOGIRI - Sintya, Intan; Listyorini , Puguh Ika; Susanto , Anton (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Hospitals, especially emergency departments (IGD), have the aim of achieving optimal health services for patients quickly and precisely and integrated in handling the emergency level so as to prevent the risk of disability and death with a response time of 5 minutes. Speed ​​in providing services in the emergency department (IGD) is a crucial factor in determining the level of patient satisfaction. This research was conducted to determine the relationship between emergency department service response time and patient satisfaction at the Muhammadiyah Selogiri Hospital using a quantitative design with a cross sectional approach. The sample in this study was 257 respondents, using a purposive sampling technique. The research instrument was a questionnaire and the data analysis used was univariate and bivariate analysis. Statistical analysis used the Spearman rho test. Based on the results of the analysis using the Spearman rho statistical test, it was found that the p value was <0.05 (0.000), so Ho was rejected and Ha was accepted, which means there is a relationship between the response time of emergency installation services and patient satisfaction at the Muhammadiyah Selogiri Hospital. Meanwhile, the correlation coefficient value is -0.462, which is interpreted as indicating that the strength of the relationship is at a low or weak level. There is a relationship between the response time of emergency services and patient satisfaction at the Muhammadiyah Selogiri Hospital. It is hoped that this research will further improve the existing response time so that quality service can be achieved and support a sense of satisfaction for patients and families who receive services.